Lower Risk of Revision Surgery After Arthroscopic Versus Open Irrigation and Débridement for Shoulder Septic Arthritis. Issue 23 (1st December 2022) - Upfill-Brown, Alexander; Shi, Brendan; Carter, Matthew; Maturana, Carlos; Hart, Chistopher; Shah, Akash A.; Brodke, Dane; Hsiue, Peter; Photopoulos, Christos; Lee, Christopher; Stavrakis, Alexandra
Abstract : Background: In the treatment of native shoulder septic arthritis, the optimal irrigation and débridement modality—arthroscopic versus open—is a matter of controversy. We aim to compare revision-free survival (RFS), complications, and resource utilization between these approaches. Methods: The National Readmission Database was queried from 2016 to 2019 to identify patients using International Classification of Diseases, 10th revision, diagnostic and procedure codes. Days to revision irrigation and débridement (I&D) were calculated for patients during index admission or subsequent readmissions. Multivariate regression was used for healthcare utilization analysis. Survival analysis was done using Kaplan-Meier analysis and Cox proportional hazard regression. Results: A total of 4, 113 patients with native shoulder septic arthritis undergoing I&D were identified, 2, 775 arthroscopic (67.5%) and 1, 338 open (32.5%). The median follow-up was 170 days (interquartile range 79 to 265). A total of 341 patients (8.3%) underwent revision I&D at a median of 9 days. On multivariate analysis, arthroscopic I&D was associated with a reduction in hospital costs of $4, 154 ( P < 0.001) and length of stay of 0.78 days ( P = 0.030). Arthroscopic I&D was associated with reduced blood transfusions (odds ratio 0.69, P = 0.001) and wound complications (odds ratio 0.30, P < 0.001). RFS was 96.4%, 94.9%, 93.3%, and 92.6% for arthroscopic I&D and 94.1%, 92.6%, 90.4%, and 89.0% for open I&D at 10, 30, 90 and 180 days, respectively ( P = 0.00043). On multivariate Cox modeling, arthroscopic I&D was associated with improved survival (hazard ratio 0.67, P = 0.00035). On stratified analysis, arthroscopic I&D was associated with improved RFS in patients aged 65 years or older ( P < 0.001), but RFS was similar in those younger than 65 years ( P = 0.17). Conclusion: Risk of revision I&D was markedly lower after arthroscopic I&D compared with open, although the protective benefit was limited to patients aged 65 years or older. Arthroscopy was also associated with decreased costs, length of stay, and complications. Although surgeons must consider specific patient factors, our results suggest that arthroscopic I&D is superior to open I&D. Level of Evidence: III